Surface modification of PdlLGA microspheres with gelatine methacrylate: evaluation of adsorption, entrapment, and oxygen plasma treatment approaches - Baki, Abdulrahman; Rahman, Cheryl V.; White, Lisa J.; Scurr, David J.; Qutachi, Omar; Shakesheff, Kevin M. (Elsevier, 2017)
Injectable poly (dl-lactic-co-glycolic acid) (PdlLGA) microspheres are promising candidates as biodegradable controlled release carriers for drug and cell delivery applications; however, they have limited functional groups on the surface to enable dense grafting of tissue specific biocompatible molecules. In this study we have evaluated surface adsorption, entrapment and oxygen plasma treatment as three approaches to modify the surfaces of PdlLGA microspheres with gelatine methacrylate (gel-MA) as a biocompatible and photo cross-linkable macromolecule. Time of flight secondary ion mass spectroscopy (TOF SIMS) and X-ray photoelectron spectroscopy (XPS) were used to detect and quantify gel-MA on the surfaces. Fluorescent and scanning electron microscopies (SEM) were used to image the topographical changes. Human mesenchymal stem cells (hMSCs) of immortalised cell line were cultured on the surface of gel-MA modified PdlLGA microspheres and Presto-Blue assay was used to study the effect of different surface modifications on cell proliferation. Data analysis showed that the oxygen plasma treatment approach resulted in the highest density of gel-MA deposition. This study supports oxygen plasma treatment as a facile approach to modify the surface of injectable PdlLGA microspheres with macromolecules such as gel-MA to enhance proliferation rate of injected cells and potentially enable further grafting of tissue specific molecules.